Implementation of The Snowball Throwing Learning Model Newton's Law Physics Song Assisted on Interest and Learning Outcomes - Umar Sulaiman; Nur Aeni Aeni; Andi Ferawati (Pendidikan Fisika UIN Alauddin Makassar, 2023)
The aim of the study was to describe the interests and learning outcomes of students who were taught using the snowball throwing learning model assisted by Newton's law physics song, to find out the differences in interest and learning outcomes taught using the snowball throwing learning model and those taught using the conventional model. This type of research is quasi-experimental with a posttest only control group design. The research population is class X students of SMAN 1 Jeneponto. The research instrument was a response questionnaire and a test of learning outcomes. Descriptive analysis of the very high category of the experimental class and the high category of the control class. Inferential analysis using the t test obtained tcount 4.68 < ttable 2.04 This shows that H0 is rejected and Ha is accepted or there are differences in student learning outcomes. The implications of this study are considerations for educators in using the snowball throwing learning model assisted by physics songs, educators can use different learning models, for other researchers it can be used as a reference for further research.